2014
DOI: 10.1007/s12026-014-8568-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22: Biomarker of maternal and fetal inflammation?

Abstract: Histologic chorioamnionitis (HCA) is an intrauterine status of inflammation which may lead to the fetal inflammatory response syndrome. Inflammation is a pathogenetic mechanism also of preeclampsia, although not of microbial origin. The aim of the present pilot study was to evaluate the pattern of inflammatory cytokines in mothers and high-risk preterm infants during the perinatal period. Concentrations of proinflammatory and anti-inflammatory cytokines and C-reactive protein were evaluated in maternal, cord, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Not surprisingly, synthetic PIF prevented the increase of those cytokines in the serum (Table 2) in line with natural killer cells being PIF`s target [23]. Finally, synthetic PIF modulated IL-22, a member of IL-10 family (Table 2) and increased IL-22 levels are an inflammatory marker of placental dysfunction and early pregnancy loss [56, 69]. …”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, synthetic PIF prevented the increase of those cytokines in the serum (Table 2) in line with natural killer cells being PIF`s target [23]. Finally, synthetic PIF modulated IL-22, a member of IL-10 family (Table 2) and increased IL-22 levels are an inflammatory marker of placental dysfunction and early pregnancy loss [56, 69]. …”
Section: Discussionmentioning
confidence: 99%
“…5 The possible association between inflammatory cytokines, inflammatory biomarkers, leukocytosis, and perinatal outcomes was shown previously. 16,17 A strong association between NLR to other conditions of uteroplacental insufficiency such as pre-eclampsia was previously described. 10 As IUGR and SGA may be the result of such placental insufficiency, it is hypothesized that NLR may be a valuable index that can be used for early prediction of SGA and IUGR.…”
Section: Introductionmentioning
confidence: 88%
“…Its signal transduction depends mainly on activation of the JAK/STAT pathway . In a pilot study by Bersani et al, IL‐22 levels were found significantly higher in the cord blood of neonates born from mothers with PE compared to controls.…”
Section: Resultsmentioning
confidence: 91%
“…Interleukin‐23 (IL‐23) is a type I heterodimeric cytokine, consisting of a 19‐kDa tetrahelical core a‐subunit (IL‐23p19) linked to IL‐12’s 40‐kDa subunit, namely IL‐12p40 . It is produced by macrophages, dendritic cells .…”
Section: Resultsmentioning
confidence: 99%